Diseño arquitectónico de un centro de desarrollo infantil para la ciudad de Pelileo - Chicaiza Masaquiza Lady Patricia (2024)
This project focused on the architectural design of a Child Development Center in the city of Pelileo, with the main objective of fostering the comprehensive development of children. Through a thorough analysis of regulations, architectural programs, and reference studies, a proposal was developed that meets the standards of child care and education. The study included a detailed diagnosis of the location to select a strategic site that ensures universal accessibility and integration with the urban environment. This research has not only enriched the academic knowledge of architectural design for child care but also significantly contributes to the improvement of infrastructures dedicated to child development in the Pelileo community, thereby promoting the well-being and development of new generations